A new Griesbachian–Dienerian (Induan, Early Triassic) ammonoid fauna from Gujiao, South China. (30th August 2018) - Dai, Xu; Song, Haijun; Brayard, Arnaud; Ware, David
Abstract: Bed-by-bed sampling of the lower portion of the Daye Formation at Gujiao, Guizhou Province, South China, yielded new Griesbachian–Dienerian (Induan, Early Triassic) ammonoid faunas showing a new regional Induan ammonoid succession. This biostratigraphic scheme includes in chronological order the late Griesbachian Ophiceras medium and Jieshaniceras guizhouense beds, and the middle Dienerian Ambites radiatus bed. The latter is recognized for the first time as a separate biozone in South China. Eight genera and 13 species are identified, including one new species, Mullericeras gujiaoense n. sp. The new data show that a relatively high level of ammonoid taxonomic richness occurred rather rapidly after the Permian/Triassic mass extinction in the late Griesbachian, echoing similar observations in other basins, such as in the Northern Indian Margin. UUID:http://zoobank.org/a24a3387-f3dd-4da4-a134-84372352a63d